Defining the Target in Cancer of the Oesophagus: Direct Radiotherapy Planning with Fluorodeoxyglucose Positron Emission Tomography-Computed Tomography. Issue 3 (March 2015) - le Grange, F.; Wickers, S.; Warry, A.; Warrilow, J.; Bomanji, J.; Tobias, J.S.
Abstract Aims Target definition in radiotherapy treatment planning (RTP) of oesophageal cancer is challenging and guided by a combination of diagnostic modalities. This planning study aimed to evaluate the contribution of single positron emission tomography-computed tomography (PET-CT) in the treatment position to RTP. Materials and methods Nineteen patients referred for radiotherapy from April to December 2008 were retrospectively identified. Two sets of target volumes were delineated using the planning CT and the 18F-fluoro-deoxy-D-glucose (18F-FDG) PET-CT data sets, respectively. Target volumes were compared in length, volume and geographic conformality. Radiotherapy plans were generated and compared for both data sets. Results PET-CT planning target volume (PET-CTPTV) was larger than the CT target (CTPTV) in 12 cases and smaller in seven. The median PTV conformality index was 0.82 (range 0.44–0.98). Radiotherapy plans conforming to normal tissue dose constraints were achieved for both sets of PTV in 16 patients (three patients could not be treated to the prescription dose with either technique due to very large target volumes and significant risk of normal tissue toxicity). Previously undetected locoregional nodal involvement seen on PET-CT in three cases was localised and included in the PTV. In nine cases, the CTPTV plan delivered less than 95% dose to 95% of the PET-CTPTV, raising concern about potential for geographical miss. Conclusion A single scan with diagnostic PET-CT in the treatment position for RTP allows greater confidence in anatomical localisation and interpretation of biological information. The use of PET-CT may result in larger PTV volumes in selected cases, but did not exclude patients from radical treatment within accepted normal tissue tolerance.